Fact Box decision support tools reduce decisional conflict about antibiotics for pneumonia and artificial hydration in advanced dementia: a randomized controlled trail. (31st August 2018) - Loizeau, Andrea J; Theill, Nathan; Cohen, Simon M; Eicher, Stefanie; Mitchell, Susan L; Meier, Silvio; McDowell, Michelle; Martin, Mike; Riese, Florian
Abstract: Background: fact Boxes are decision support tools that can inform about treatment effects. Objectives: to test whether Fact Box decision support tools impacted decisional conflict, knowledge and preferences about the use of antibiotics and artificial hydration in advanced dementia. Design: randomized controlled trial. Setting: Swiss-German region of Switzerland. Subjects: two hundred thirty-two participants (64 physicians, 100 relatives of dementia patients, 68 professional guardians) randomly allocated to intervention ( N = 114) or control ( N = 118). Intervention: two-page Fact Box decision support tools on antibiotics for pneumonia and artificial hydration in advanced dementia (at 1-month). Methods: participants were mailed questionnaires at baseline and one month later that asked questions about treatments based on hypothetical scenarios. The primary outcome was change in decisional conflict (DCS-D; range 0 < 100) about treatment decisions. Secondary outcomes included knowledge about treatments (range 0 < 7) and preferences to forego treatments. Results: participants were: mean age, 55.6 years; female, 62.8%. Relative to control participants, intervention participants experienced less decisional conflict about using antibiotics (unstandardized beta ( b ) = −8.35, 95% Confidence Interval (CI), −12.43, −4.28) and artificial hydration ( b = −6.02, 95% CI, −9.84, −2.20) at 1-month compared to baseline. Intervention participants displayed greater knowledge about the use of antibiotics ( b = 2.24, 95% CI, 1.79, 2.68) and artificial hydration ( b = 3.01, 95% CI, 2.53, 3.49), and were significantly more likely to prefer to forego antibiotics (odds ratio, 2.29, 95% CI, 1.08, 4.84) but not artificial hydration. Conclusions: fact Box decision support tools reduced decisional conflict, increased knowledge and promoted preferences to forego antibiotics in advanced dementia among various decision-makers. Trial registration: FORSbase (12091).